2022
DOI: 10.1007/s41685-022-00255-6
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of the COVID-19 outbreak in Turkey: analysis of vulnerability and resilience of regions and diversely affected economic sectors

Abstract: The COVID-19 outbreak has deeply affected the global economy of most countries and Turkey is no exception. However, the impacts of the outbreak differ on a regional basis, and both scientists and policymakers have neglected this regional differentiation. In an attempt to redress this situation, our study aimed to reveal the regional disparities related to the economic impacts of the outbreak and the dynamics that created this differentiation in Turkey. Our statistical analyses were carried out based on two dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…Besides, Sargento and Lopes (2023) showed a positive relationship between research and innovation organizations that cooperate with companies on innovation projects and the economic resilience of Portuguese municipalities. On the other hand, Tuysuz et al (2022) showed that both the number of patents per capita and export levels per capita predicted negatively the resilience of Turkish regions. In the same vein, employing a cluster analysis based on industrial production and retail turnover indices, Chernova and Gridnev (2023) suggested that the least resilient regions in Russia were those with higher levels of economic openness, more urbanized, and with a higher number of innovation-investing companies.…”
Section: Can Innovation Predict Regional Resilience? An Econometric E...mentioning
confidence: 99%
See 3 more Smart Citations
“…Besides, Sargento and Lopes (2023) showed a positive relationship between research and innovation organizations that cooperate with companies on innovation projects and the economic resilience of Portuguese municipalities. On the other hand, Tuysuz et al (2022) showed that both the number of patents per capita and export levels per capita predicted negatively the resilience of Turkish regions. In the same vein, employing a cluster analysis based on industrial production and retail turnover indices, Chernova and Gridnev (2023) suggested that the least resilient regions in Russia were those with higher levels of economic openness, more urbanized, and with a higher number of innovation-investing companies.…”
Section: Can Innovation Predict Regional Resilience? An Econometric E...mentioning
confidence: 99%
“…On the one hand, several positive features of exports are highlighted, such as access to new resources and markets (Bathelt et al, 2013;Walther et al, 2011), incentive for companies to maintain innovation efforts in times of crisis (Holl & Rama, 2016), and protection from shocks restricted to the national level (Martin & Gardiner, 2019). On the other hand, dependence on exports is related to the vulnerability of a region, due to greater exposure to shocks coming from other countries (Diodato & Weterings, 2015;Du et al, 2019;Eraydin, 2016a;Martin et al, 2016;Martin & Gardiner, 2019;Tuysuz et al, 2022). There is even a suggestion that small export-oriented economies may have a pattern of economic resilience depending more on extra-regional factors than on the internal context and endogenous capacities (Ženka et al, 2019).…”
Section: Can Innovation Predict Regional Resilience? An Econometric E...mentioning
confidence: 99%
See 2 more Smart Citations
“…Addressing the neglected regional dimension of the economic impacts of the COVID-19 outbreak, Tuysuz et al ( 2022 ) analyze the vulnerability and resilience of regions and diversely affected economic sectors in Turkey. They first offer a great picture of resilient and vulnerable regions by developing a resilient-vulnerability index and employing Location Quotient (LQ) analysis.…”
Section: Social and Economic Implications Of Covid-19 Pandemic And Di...mentioning
confidence: 99%